A study on implementation of green interior and sustainability from Islamic perspective in new interior design courses: new interior design department, International Islamic University Malaysia - Jasmani, Ismail (Kulliyyah of Architecture and Environmental Design, IIUM, 2013)
Interior design, as a field of study, is a rapidly growing area of interest for the last 2 years particularly for students in Centre Foundation Student (CFS), International Islamic University Malaysia. Part of this interest stems from the information of friends, television media and other source such as advertisements, interesting job and etc. Some of the educators and curriculum specialists in the nation perceive the study of interior spaces as a ‘practical application’ of the knowledge, arts, and psychology.